Effect of Educational Guidelines on Adherence of Patients with Viral Hepatitis C toward New Oral Therapeutic Regimen - Sahar A. Hassan; Salwa S. Kamel; Manal S. Hassan; Asmaa A. Saleh (Evidence-Based Nursing Research)
Context: Viral hepatitis was estimated to be the seventh leading cause of mortality globally. One of the countries most affected by the hepatitis C virus is Egypt.